Swearing Words in Holy Scriptures: A Pragmatic Study of the Quran - Reranta, Redika Cindra; Setiawan, Rifki Hanif; Putri, Elsa Hana Rahma; Safira, Tiara Putri (Universitas Teknokrat Indonesia, 2024)
The term